Tuning in to Toddlers: Research Protocol and Recruitment for Evaluation of an Emotion Socialization Program for Parents of Toddlers - Havighurst, Sophie S.; Kehoe, Christiane E.; Harley, Ann E.; Johnson, Ameika M.; Allen, Nicholas B.; Thomas, Rae L. (Frontiers in Psychology, 2019)
Background: Parenting a toddler is a challenging experience for many parents with times of emotional dysregulation in both parent and child. Parenting interventions may be useful for parents to improve in their emotion regulation as well as developing skills in responding to children’s emotions that assist the child to understand and regulate emotions (emotion competence). Tuning in to Toddlers (TOTS) is a new parenting program that aims to improve parents’ emotional responsiveness, coaching and emotion regulation (aspects of emotion socialization) to promote optimal emotional development in toddlers, and prevent social and behavioral difficulties. This paper outlines the rationale, methodology, intervention and recruitment process used in a trial to establish program efficacy. Method/Design: Parents of toddlers aged 18-36 months old were recruited through child care centers (CC) and maternal child health (MCH) centers in Melbourne, Australia and were allocated to either intervention or a 15-month wait-list control condition in a cluster-randomized controlled design. Inclusion criteria were a child in the age range at baseline attending one of the CC or MCH centers. Exclusion criteria were if the parent/carer had insufficient English to attend the intervention and complete measures. Parents in the intervention condition participated in the 6-session group TOTS program delivered by 2 facilitators using a structured manual and measures of program fidelity and acceptability. Participants in the wait-list control condition received the intervention after a 15-month waiting period. Participants completed measures at baseline, post- intervention (intervention participants only) and 15-month follow-up. Primary outcome measures included parent emotion socialization (self-report and observed). Secondary outcomes included parent-reported parent functioning and toddler social, emotional and behavioral functioning, and parent and toddler systemic cortisol stress (using hair samples). The study was designed to comply with the CONSORT statement and intervention reporting outlined using TIDieR. Results: Three hundred and six parents were recruited and completed baseline parent questionnaires, with a further 234 completing parent-child observation assessments, 235 parent cortisol, and 198 child cortisol. Discussion: This paper is a methodological description of the TOTS randomized controlled trial evaluation protocol. It outlines some of the challenges in recruiting parents of toddlers to parenting programs.